TECHNOLOGY-ENHANCED LANGUAGE LEARNING (TELL) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Technology-Enhanced Language Learning (TELL) refers to the integration of digital tools and technological innovations to facilitate and improve language acquisition. This approach has revolutionized traditional language learning methods by incorporating artificial intelligence (AI), virtual reality (VR), mobile applications, and online learning platforms. TELL provides learners with interactive and personalized experiences, enabling them to practice listening, speaking, reading, and writing skills in authentic contexts. The effectiveness of TELL is evident in its ability to enhance motivation, provide immediate feedback, and offer adaptive learning paths. This paper explores the role of TELL in modern language education, examining its benefits, challenges, and future directions.